Analysis of The Development of Terrorist Groups In The Jurisdiction of The Sidoarjo Police Office - Yosep Putra Sudibyo; Alif Bryan Pradana Kusuma; Andi Gibran Gani Mandica (Tanggon Kosala, 2024)
The study "Analysis of the Development of Terrorist Groups in the Sidoarjo Police Jurisdiction" investigates the activities of terrorist groups in the Sidoarjo area, analyzes the driving factors, and evaluates early detection efforts. This study uses the mixed method embedded model to explore various aspects of terrorism. It was revealed that early detection by the Sidoarjo Police Security Intelligence Unit was hampered by equipment damage, inefficient budget allocation, and inadequate program management systems. This indicates the need to strengthen and improve efforts to prevent terrorism in the region. This study also highlights the driving factors for the development of terrorist groups, such as the evolution of tactics and techniques, the social conditions of apathetic and easily provoked communities, and the existence of individuals/groups who take advantage of terrorist groups for specific purposes. In addition, worrying developments were also found in the Sidoarjo terrorist group, including the ability to make weapons, youth cadre programs, and support for terrorist groups abroad. Other significant findings are the identification of essential figures in the local Jamaah Islamiyah group, such as Usman Bin Sheff, Umar Patek alias Hisyam, and Zulkarnaen, as well as the phenomenon of former terrorist convicts returning to the terror network even though they have pledged allegiance to the Republic of Indonesia. This research is expected to contribute to the scientific study of terrorism, enrich the understanding of the community and security forces regarding the dynamics of terrorist groups, and increase public awareness of the threat of terrorism.